(untitled) (Journal of Geography and Environmental Management, 2017)
The Issyk-Kul Lake is one of the largest highland and brackish lakes in continental origin. Assessment and analysis of the long-term dynamics on the chemical composition of the water in the Issyk-Kul Lake basin was carried out according to the data for 1932, 1977 and 1986. The average long-term dynamics of lake water salinity was determined from the data for 1928, 1960, 1980, 2000 and 2014. Sulfates, chlorides, sodium and magnesium are the predominant ions of lake water. Na+ and Mg+ predominate from the cations, and from the anions Cl- and SO4 2-. The sulfates predominate in the chemical composition of water, and the lake water belongs to the sulfate class and to the chloride-sulphate-sodium-magnesium type of mineralization. The water in the lake has an alkaline reaction and the pH of the lake water was within 7.95-8.82 in 2015. The salinity of the Issyk-Kul lake was 6.22 g/l. The study of the hydrochemistry of natural waters is of great practical importance in various branches of the economy. Since the chemical composition of water is taken into account when using natural waters for all types of water supply and water use. The importance of hydrochemical research is also increasing due to pollution of water bodies and anthropogenic activities.